O Contributo da União Europeia na Governança do Ártico: The European Union Contribution to the Governance of the Arctic - Cuogo, Francisco (Perspectivas - Journal of Political Science, 2019)
The Arctic is a region that, although located in the far north of the globe and surrounded by a small number of countries, namely the Arctic States, has gained worldwide attention. The views that converge on the north polar circle essentially follow four main aspects in the region: environmental changes; the unfolding of relations between Arctic states; the opportunities for new navigation rotation and the exploitation of natural resources. Although the last three aspects are conditioned by the first, there is no natural determinism based on environmental changes that is responsible for the scenario that is being built in the region. On the contrary, cooperation underway in the Arctic is a result of governance in the region that has led to relations between the actors in the North Polar Circle and cooperative relations. However, even if cooperation is the current condition, world interests in the Arctic can cause destabilization in this geopolitical scenario. Therefore, we analyze in this article how an actor with the characteristics of the European Union (EU) can bring effective contributions to Arctic governance. For the region has increasingly attracted the eyes of non-Arctic actors, such as China, India, Japan, Germany, etc., and their presence in the North Polar Circle, strongly oriented towards economic purposes, may threaten peace in the Arctic. The EU, however, in addition to having a strong regulatory capacity, is also an actor who exercises global influence of values and norms, and seeks to articulate cooperative relations in its practices and discourses. And therefore, it can contribute to the maintenance of Arctic peace, in the 21st century, when global interests and non-Arctic actors in the region emerge. Resumo O Ártico é uma região que, apesar de situada no extremo norte do globo e cercada por um número reduzido de países, nomeadamente os Estados do Ártico, tem conquistado a atenção mundial. Os olhares que convergem para o círculo polar norte acompanham fundamentalmente quatro aspectos principais ...